2016
DOI: 10.3389/fpls.2016.01047
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Ribosomal DNA ITS2 Region of Physalis (Solanaceae): DNA Barcoding and Phylogenetic Study

Abstract: Recently, commercial interest in Physalis species has grown worldwide due to their high nutritional value, edible fruit, and potential medicinal properties. However, many Physalis species have similar shapes and are easily confused, and consequently the phylogenetic relationships between Physalis species are poorly understood. This hinders their safe utilization and genetic resource conservation. In this study, the nuclear ribosomal ITS2 region was used to identify species and phylogenetically examine Physalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 56 publications
(100 reference statements)
3
65
0
2
Order By: Relevance
“…Physalis is one of the important genera of the plant family Solanaceae, comprising ranged from 75 to 120 species (Maggie 2005;Martinez 1998;Chinese Academy of Sciences 1978;Wei et al 2012). Most Physalis species are distributed in tropical and temperate regions of the Americas, and a few species are native to Eurasia and Southeast Asia (Feng et al 2016;Maggie 2005;Martinez 1998;Chinese Academy of Sciences 1978;Wei et al 2012). In China, there are five Physalis species (Physalis alkekengi, P. angulate, P. peruviana, P. pubescens, and P. minima) and two varieties (P. alkekengi var.…”
Section: Introductionmentioning
confidence: 99%
“…Physalis is one of the important genera of the plant family Solanaceae, comprising ranged from 75 to 120 species (Maggie 2005;Martinez 1998;Chinese Academy of Sciences 1978;Wei et al 2012). Most Physalis species are distributed in tropical and temperate regions of the Americas, and a few species are native to Eurasia and Southeast Asia (Feng et al 2016;Maggie 2005;Martinez 1998;Chinese Academy of Sciences 1978;Wei et al 2012). In China, there are five Physalis species (Physalis alkekengi, P. angulate, P. peruviana, P. pubescens, and P. minima) and two varieties (P. alkekengi var.…”
Section: Introductionmentioning
confidence: 99%
“…In the nuclear genome, the ITS gene, especially ITS2, is a potential DNA barcode, and it has been used in multi‐loci barcode combinations (Chase et al., ; Feng et al., ). Schultz et al.…”
mentioning
confidence: 99%
“…() tested the discriminatory ability of ITS2 in more than 6600 plant samples belonging to 4800 species from 753 distinct genera, and proposed that it can be used as a standard DNA barcode to identify medicinal plants. ITS2 has since been shown to be a promising and effective region for identifying medicinal samples (Feng et al., ; Han et al., ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In acarological research, the internal transcribed spacer ITS-2 gene has been used to study organization and kinship of a population, and to 16 identify taxonomically challenging species. Previous literature showed that the ITS-2 region has been used as a genetic marker for scrutinizing the diversity and exploring phylogenetic relationships 17 among astigmatid mites. ITS-2 marker has been used to successfully verify the taxonomy of closely related species and to differentiate and identify 18,19 different species of astigmatid mites.…”
Section: Phylogenetic Analysis Of Astigmatid Mites Sarcoptes Scabiei mentioning
confidence: 99%